Expressions of Localities: Positionalities and "Powerful Particulars" - Jose, Ricardo T.; Cruz, Elinor May K. (Kasarinlan: Philippine Journal of Third World Studies, 2020)
Introduces the content of  Kasarinlan: Philippine Journal of Third World Studies , volume 33, number 2 (2018), "Localities."